Water quality and risk assessment of select heavy metals in Tilapia Oreochromis niloticus from Pulang Lake, THE Philippines (Philippine Journal of Science, 2024)
Regular monitoring of the water quality and heavy metal concentration in edible fish from the Pulangi Lake – an artificial lake in Bukidnon, the Philippines – has not yet been established. This study analyzed the water quality of the Pulangi Lake and assessed the associated risks of heavy metals cadmium (Cd), chromium (Cr), and lead (Pb) in Nile tilapia (Oreochromis niloticus) harvested from the lake during the dry season. Key informant interviews (KII) were also conducted to gather relevant information about the lake. The physico-chemical analysis of the surface water revealed high fecal coliform levels, exceeding the standard limit by more than 100%, but the concentrations of Cd, Cr, and Pb were below the standard limit. However, the Cr concentration in tilapia (0.2430–1.7870 mg/kg) exceeded the permissible limit of 0.05 mg/kg set by the Food and Agriculture Organization and the World Health Organization. Low concentrations of Cd (0.0270–0.1140 mg/kg) and Pb (0.0360–0.4350 mg/kg) were observed. The risk assessment of these individual heavy metals measured from tilapia and its combined impacts showed no potential non-carcinogenic effects based on the estimated target hazard quotient (THQ < 1) and hazard index (HI < 1). However, based on the permissible target cancer risk (1x 10–6 to 1 x 10–4), tilapia from the Pulangi Lake should be reexamined as it appears that – in terms of Cd and Cr – the probability relating to contamination problem can occur. The present study can be used as baseline data for risk management.